Mapping multi-dimensional variability in water stress strategies across temperate forests - Liu, Daijun; Esquivel-Muelbert, Adriane; Acil, Nezha; Astigarraga, Julen; Cienciala, Emil; Fridman, Jonas; Kunstler, Georges; Matthews, Thomas J.; Ruiz-Benito, Paloma; Sadler, Jonathan P.; Schelhaas, Mart-Jan; Suvanto, Susanne; et al. (Springer Nature, 2024)
Increasing water stress is emerging as a global phenomenon, and is anticipated to have a marked impact on forest function. The role of tree functional strategies is pivotal in regulating forest fitness and their ability to cope with water stress. However, how the functional strategies found at the tree or species level scale up to characterise forest communities and their variation across regions is not yet well-established. By combining eight water-stress-related functional traits with forest inventory data from the USA and Europe, we investigated the community-level trait coordination and the biogeographic patterns of trait associations for woody plants, and analysed the relationships between the trait associations and climate factors. We find that the trait associations at the community level are consistent with those found at the species level. Traits associated with acquisitive-conservative strategies forms one dimension of variation, while leaf turgor loss point, associated with stomatal water regulation strategy, loads along a second dimension. Surprisingly, spatial patterns of community-level trait association are better explained by temperature than by aridity, suggesting a temperature-driven adaptation. These findings provide a basis to build predictions of forest response under water stress, with particular potential to improve simulations of tree mortality and forest biomass accumulation in a changing climate.
Keywords: water stress; temperate forests